THE EFFECT OF ASSERTIVE COMMUNITY TREATMENT TOWARDS ANXIETY AND DEPRESSION ON BREAST CANCER CLIENT - Andikawati Fitriasari; Ahmad Yusuf; Ririn Probowati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
Background: Breast cancer increases the occurrence of psychosocial problems, namely anxiety and depression. Anxiety and depression have shown an effect on the quality of life. Assertive Community Treatment is a psychosocial service that involves the family's role in overcoming breast cancer client anxiety and depression.Objective: This study aimed to determine the effect of Assertive Community Treatment towards anxiety and depression of breast cancer clients.Method: The research design used was quasi-experiment with a pre-posttest control group design. This research subject determines by using purposive sampling. The study population was breast cancer clients who seek treatment at Public Health Center of Medokan Ayu in Surabaya. The sample is breast cancer clients who have inclusion criteria a) age 30-60 years old, b) live with her partner, c) has chronic pain ± 1-5 years. The instrument is PDQBC (Psychosocial Distress Questionnaire Breast Cancer subscales anxiety and depression. Data analysis used paired T-Test and Independent T-Test.Result: Paired T test results showed anxiety values in the treatment group p = 0.000, depression value p = 0.001. The results of the independent T test statistic obtained p value = 0.000 showed a significant difference between anxiety and depression of breast cancer clients in the control group and the treatment group.Conclusion: Assertive Community Treatment provides a good impact in order to reduce the level of anxiety and depression in clients with breast cancer. Assertive Community Treatment (ACT) is recommended to be given by teams. Key words: Assertive Community Treatment, Anxiety, Depression, Breast Cancer Clients, Palliative.